SOSIALISASI DAN PENDIDIKAN PEMILIH MELALUI METODE SIMULASI UNTUK MENINGKATKAN AKSESIBILITAS BAGI PENYANDANG DISABILITAS (Studi kasus pada Pemilihan Gubernur dan Wakil Gubernur Jawa Barat Tahun 2018 di Kabupaten Bandung) - Agus Hasbi Noor; Ansori Ansori (Universitas Sriwijaya, 2019)
This study aims to describe the socialization and voter education for disabilities in the Election of Governor and Deputy Governor of West Java in Bandung, 2018. This is a qualitative desctiptive, the data used were from observation, interviews and documentation. The sample used were purposive sampling which consist of the organizer of election in Bandung, participants with disabilities, and other election participants. The result shows that there were obstacles related to fill the right of participants with disabilities especially about the limit access of information and there were a dichotomy of participants and organizer about the disabilities existence. The impact of using simulation method focused on improving voting procedures and has not increase the political intelligent of participants with disable yet. This study not only can be used as a basis data for further research related to various strategic to fill the rights for participants with disabilities, but also can make a positive contribution to improve the quality of elections in Indonesia.